2015
DOI: 10.11604/pamj.2015.20.111.5012
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia in a restless eclamptic with undiagnosed second twin: case report

Abstract: The use of sub-arachnoid block in a restless eclamptic is not very common. Studies have demonstrated some benefits of sub-arachnoid block over general anaesthesia in stable eclamptic but its role in the management of unstable eclampsia has not been established. Reported below is an eclamptic parturient who was restless despite magnesium sulphate regimen and possesed features suggestive of difficult airway who had uneventful subarachnoid- block for caesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…There are controversies surrounding the appropriate anaesthetic technique for preeclamptic and eclamptic parturients. Safety of spinal anaesthesia was studied by Razzaque et al and Afolayan et al and they concluded that spinal anaesthesia is safer than general anaesthesia for eclamptic women who are conscious (23,24). This finding is in concordance with our findings as mortality was more in general anaesthesia (47%) as compared to in subarachnoid block (SAB) (1.8%).…”
Section: Discussionsupporting
confidence: 91%
“…There are controversies surrounding the appropriate anaesthetic technique for preeclamptic and eclamptic parturients. Safety of spinal anaesthesia was studied by Razzaque et al and Afolayan et al and they concluded that spinal anaesthesia is safer than general anaesthesia for eclamptic women who are conscious (23,24). This finding is in concordance with our findings as mortality was more in general anaesthesia (47%) as compared to in subarachnoid block (SAB) (1.8%).…”
Section: Discussionsupporting
confidence: 91%